Influence of Water System Connectivity Project on Hydrodynamics of Offshore Tidal Waters - WANG Yifei; WANG Yanhong; YANG Xiaoyu; JIAO Jian; DING Lei (Renmin Zhujiang)
Tidal waters refer to rivers, lakes, and other water bodies with periodic water level and velocity changes in coastal areas affected by offshore tides. The water system connectivity project adopts a series of artificial or natural measures to connect the water system and realize the hydraulic connection between the rivers. In this study, a two-dimensional hydrodynamic mathematical model was used to simulate the hydrodynamic conditions in the Longjiang Pond before and after the construction of the Longjiang River System Connectivity Project. The results show that the water flow velocity in most areas before and after the construction of the project is smaller than 2 cm/s, and the water flow velocity in some areas with poor water exchange capacity is smaller than 0.5 cm/s. The hydrodynamic conditions in the north lake area are obviously weaker than those in the south lake area, and the hydrodynamic conditions in the dry season and the rainy season are not much different. The net water flux before and after the construction of the project is basically similar, but the total amount of water exchange after the construction of the project is much larger than that before the construction of the project. During the flood tide, the flow velocity in the lake area and the connection section after the construction of the project is significantly reduced, while the flow velocity in the lake area and the connection section after the construction of the project is significantly increased during the ebb tide. Since the project itself has no additional power, the project only significantly improves the water dynamics in the waters near the two connected engineering channels. Therefore, it is recommended to add pumping stations in the connected channels of the two water systems or add water replenishment points in some areas with poor improvement effects to increase local water mobility.